The great American whatever [compact disc, unabridged] - Federle, Tim (Audioworks (Children's), an imprint of Simon & Schuster Audio Division, 2016)
Quinn Roberts is a sixteen-year-old smart aleck and Hollywood hopeful whose only worry used to be writing convincing dialogue for the movies he made with his sister Annabeth. Of course, that was all before Quinn stopped going to school, before his mom started sleeping on the sofa, and before Annabeth was killed in a car accident. Enter Geoff, Quinn's best friend who insists it's time that Quinn came out-- at least from hibernation. One haircut later, Geoff drags Quinn to his first college party, where instead of nursing his pain, he meets a guy, and falls hard. What follows is an upside-down week in which Quinn begins imagining his future as a screenplay that might actually have a happily-ever-after ending.